Tuning the selectivity of light hydrocarbons in natural gas in a family of isoreticular MOFs. Issue 22 (18th May 2017) - Grancha, Thais; Mon, Marta; Ferrando-Soria, Jesús; Gascon, Jorge; Seoane, Beatriz; Ramos-Fernandez, Enrique V.; Armentano, Donatella; Pardo, Emilio
Abstract : The kinetic adsorption selectivity of methane versus other light hydrocarbons, present in natural gas, is tuned in a rationally synthesized family of isoreticular MOFs. Abstract : Purification of methane from other light hydrocarbons in natural gas is a topic of intense research due to its fundamental importance in the utilization of natural gas fields. Porous materials have emerged as excellent alternative platforms to conventional cryogenic methodologies to perform this task in a cost- and energy-efficient manner. Here we report a new family of isoreticular chiral MOFs, prepared from oxamidato ligands derived from natural amino acidsl -alanine, l -valine andl -leucine, where, by increasing the length of the alkyl residue of the amino acid, the charge density of the MOF's channels can be tuned (1 >2 >3 ), decreasing the adsorption preference towards methane over light hydrocarbons thus improving this purification process. The validity of our rational design strategy has been proved by a combination of single-component adsorption isotherms, adsorption kinetics of CH4, C2 H6, C3 H8 and n -C4 H10, and breakthrough experiments of binary CH4 /C2 H6 and CH4 /C3 H8 mixtures.